The Effect of Stakeholder Pressure on Sustainability Report Exposition - Adeng Pustikaningsih; Karunia, Anisah Novi; Buchori, Willa Putri Malinda; Septiningdyah Arianisari; Ardhana Reswari Hasna Pratista; Indarto Waluyo (Journal of Vocational Applied Research and Studies, 2024)
There is a phenomenon of increasing demand for transparency in non-financial information, moving towards integrated reporting. Companies are increasingly conducting materiality evaluations to identify and prioritize sustainability issues that are most significant for their business and stakeholders. This research aimed to determine the influence of stakeholder pressure, which consists of investors, creditors, suppliers, and consumers, on the issuance of sustainability reports. This study was quantitative in nature. The data source for this research were secondary data derived from the financial reports of manufacturing sector companies from 2014 to 2021. The data were processed using SPSS version 25. The findings reveal that stakeholder pressure, particularly from investors and creditors, has a significantly positive impact on the issuance of sustainability reports. This indicates that investors and creditors play a crucial role in encouraging companies to publish sustainability reports in each accounting period. Meanwhile, the pressure from suppliers and consumers shows no significant effect on sustainability reporting. This is because suppliers generally tend to prioritize operational aspects and daily business relationships over corporate sustainability reporting. Similarly, sustainability reports are not a primary consideration in consumers' decision-making processes.